El español en la Suiza alemana: características léxicas de la segunda generación de hispanohablantes - Jiménez Ramírez, Félix (ELUA: Estudios de Lingüística. Universidad de Alicante, 2000)
The linguistic situation of the second generation of Spaniards in the German-speaking part of Switzerland is the result of the contact of different languages and multilingualism. Their Spanish is determined by German, Swiss-German, Italian and oven French influences. The reason for their desviation from standard Spanish lies in the fact, that their scholar education is in the local language and that they only learn and use spoken Spanish at home. The desviation from standard Spanish is not to be interpreted as symptoms of language attrition, but as the result of their linguistic competence in various languages. This paper presents and analyses the lexical characteristic of the second generation of Spanish-speaking people in the German-speaking part of Switzerland.